Dissociation of storage and rehearsal in verbal working memory: evidence from positron emission tomography. - Awh, Edward; Jonides, John; Smith, Edward E. (Psychological Science., 1996)
A study was conducted, through the use of positron emission tomography, to provide further evidence for the hypothesis that the working memory system for verbal information has two components: a phonological store and a rehearsal mechanism that refreshes the contents of this store. In the first experiment, participants conducted a variant of S. Sternberg's (1966) item recognition task; in the second experiment, a continuous memory task was employed with control conditions designed to divide the brain regions underlying storage and rehearsal. The findings demonstrated that independent brain regions mediated storage and rehearsal. In the final experiment, a dual-task procedure provided support for the assumption that these memory tasks elicited a rehearsal strategy.